Mesalazin-induced eosinophilic pneumonia in a 15-year-old boy with ulcerative colitis - G. N. Yankinа; L. V. Gorlenko; E. V. Loshkova; E. I. Kondratyeva; E. Yu. Tuteva; A. A. Terenteva; V. A. Zhelev; E. V. Mikhalev; T. A. Shemyakinа; T. S. Krivonogova; N. A. Ryzhakova; E. V. Romanova (Бюллетень сибирской медицины)
One of the most difficult categories of patients is patients with inflammatory bowel disease. A clinical case of the development of mesalazine-induced eosinophilic pneumonia in a 15-year-old boy with ulcerative colitis is presented. The patient suffered an acute respiratory disease, which caused the aggravation of ulcerative colitis and, accordingly, an increase in the dose of mesalazine. Against this background, the child had active complaints of heaviness in the chest to the left. Eosinophilia was noted in the blood. Analysis of clinical symptoms, X-ray data, microscopic examination of the pleural fluid, the results of spiral computed tomography of the chest allowed a differential diagnosis of the main symptoms and associated identified pulmonary lesions with mesalazine.